Physico-chemical Parameters of Panchakavya from Different Samples - S, Sornalatha. (International Journal of Pharmaceutical & Biological Archive, 2016)
Panchagavya is an organic formulation made from cow goods. The usage of fermented organic formulations with supportive beneficial microorganisms as foliar nourishment has been come into the picture of modern agriculture for giving rise to good quality non residue protected food. Panchakavya has played a significant role in providing resistance to pests and diseases, resulting in increased overall yields. Panchakavya possess the properties of fertilizers and biopesticides.PanchgavyaTherapy/Chikitsa(Cowpathy) has been proposed as an alternate prophylactic and therapeutic approach for sound livestock and poultry health along with safeguarding human health. Its antimicrobial properties have gained the attention of the medical and veterinary professionals. Panchagavya in appropriate dilutions has been found as promising growth enhancer of micro-organism hence it adds to the soil fertility by avoiding the use of chemical fertilizers, and with marked antifungal properties it can be used as a successful microbiological growth medium as well. Panchagavya at higher dilution are found to be promising source for simple and naturally derived bacteriological media that are less expensive because of additional antifungal effect with growth promotion. The physical parameters of panchakavya such as temperature,pH,moisture content and electrical conductivity. The chemical parameters of panchakavya like nitrogen, phosphorus, potassium, calcium, magnesium etc .To analyze and compare the physico-chemical parameters of two different samples.